The effects of the implementation of modern media in the teaching of Serbian language and literature - Dmitrić, Marijana (Norma, 2024)
This paper aims to determine the contribution of the media in the teaching of Serbian language and literature in the younger grades of elementary school. The methodological part of the research is an experimental research with parallel groups in which the effects of media use are examined. In the research, a descriptive and experimental method was used in the collection of data, during the processing and interpretation of the research results. The instruments used in the research are the initial knowledge test and the final knowledge test. The population consists of students of younger grades of "Petar Petrović Njegoš" Elementary School in Vrbas. Through research, we wanted to examine whether modern media such as comics, films, computers, educational software, etc. contribute to creativity, motivation, maintenance of attention and longevity of knowledge in students compared to the traditional approach in teaching. By analyzing the results of the research, we proved that the use of media in the teaching of Serbian language and literature led to better results compared to the group that did not use media. With these results, we want to point out the importance of the use of media in the system of education and upbringing, and therefore we want to motivate teachers to use media more often in the teaching of the Serbian language.